Contributios to the Flora of Dimban Ghats and Adjoining Areas of Coimbatore District, Tamilnadu State - Subramanian, K. N.; Kalyani, K. B. (Indian Forester, 1977)
A general description of the vegetation of the area with an enumeration of the species are provided in this paper.